Derivational Morphology in Urdu: A Lexical Morphology Approach - Muhammad Safdar; Riaz Ahmed Mangrio (Linguistics and Literature Review, 2021)
From the theoretical perspective of lexical morphology (LM), this paper analyzes neutral and non-neutral affixes and their general organizational position in the morphology of derived words in Urdu. It explores the properties and behavior that Urdu affixes exercise during their attachment or insertion into roots/bases to produce new words, to question the assumptions of LM. Nine hundred and eighty sample words were randomly selected from our observations, articles in Urdu newspapers, and Urdu news television channels in Pakistan. While LM helps a lot regarding the analysis of neutral and non-neutral affixes, its assumptions concerning the hierarchical organization of affixes in derived word-formations do not correspond with the morphology of words in Urdu. This paper contributes as an initial step toward formulating a theory of the morphology of derived words in Urdu – a language rarely theoretically analyzed regarding the morphology of its derived words.Keywords: Morphology, derivation, lexical, Urdu, Pakistan